1996
DOI: 10.1056/nejm199607113350202
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Artemether or Quinine in Vietnamese Adults with Severe Falciparum Malaria

Abstract: Artemether is a satisfactory alternative to quinine for the treatment of severe malaria in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
267
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(275 citation statements)
references
References 17 publications
7
267
1
Order By: Relevance
“…Seven had cerebral malaria and recovered consciousness in 26-69 hr, which is similar to values observed in an earlier study in which quinine was used (mean Ϯ SEM ϭ 47.4 Ϯ 3.2 hr) 2 and in a recent large Vietnamese study of adults (median ϭ 66 hr, range ϭ 0-828 hr). 12 The initial parasite counts include some very high values (8 more than 400,000/l) but were again in the same range observed in previous studies. Treatment with intravenous artesunate resulted in parasite clearance in 29-86 hr and combined with the longer-acting mefloquine prevented any reoccurrence of parasitemia.…”
Section: Discussionsupporting
confidence: 85%
“…Seven had cerebral malaria and recovered consciousness in 26-69 hr, which is similar to values observed in an earlier study in which quinine was used (mean Ϯ SEM ϭ 47.4 Ϯ 3.2 hr) 2 and in a recent large Vietnamese study of adults (median ϭ 66 hr, range ϭ 0-828 hr). 12 The initial parasite counts include some very high values (8 more than 400,000/l) but were again in the same range observed in previous studies. Treatment with intravenous artesunate resulted in parasite clearance in 29-86 hr and combined with the longer-acting mefloquine prevented any reoccurrence of parasitemia.…”
Section: Discussionsupporting
confidence: 85%
“…In the early Chinese studies, neutropenia was reported, 17 but no significant changes in leukocyte counts were noted this study. Hemoglobinuria had been reported in previous studies with artemether and artesunate 24,25 and occurred in three patients in this study. All had high parasite counts (104,000-790,000/l).…”
Section: Discussionsupporting
confidence: 82%
“…The patients were part of a large double-blind trial of artemether versus quinine for the treatment of severe malaria in Viet Nam. 13 Two groups were defined prospectively, CM (n ϭ 28) and non-CM (n ϭ 26). CM was defined according to established World Health Organization guidelines as a Glasgow Coma score of 11 or less during the episode of severe malaria, 14 other causes of unconsciousness having been excluded, (eg, hypoglycemia, meningitis, or other encephalopathy) by clinical, biochemical, and cerebrospinal fluid (CSF) examination.…”
Section: Case Selectionmentioning
confidence: 99%